The other one in the Iraqi novel, Girls of Lalish, is a choice - HASAN MANSOOR MOHAMMED ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The Other One in the Iraqi Novel " Lalish’s Daughters" as an Example This paper tries to investigate the Iraqi novel after the American invasion and ISIS occupation to the Northern Iraq , to portray the Yazidi ego: its struggle and the loss of identity against the other one represented by ISIS (Daesh). The relationship between the ego and the other one in this study is not of that type of binaries such as heritage and modernism , east and west . The novel tells us the pains of the Yazidi ego. It is a witness narrating that period of occupation. The struggle in this novel is not balanced against the question " who am I?" because the other one doesn’t recognize the Yazidi ego. Moreover, the Yazidi ego speech is closed to the Yazidi community and isolated from its surroundings represented by other communities. The novel under investigation represents a good example of Iraqi novel . It is a source of inspiration, a blog to record events and situations that the Yazidi community has undergone. Moreover, it is a portrayal of the Yazidi ideology. It also describes the brutality of the other one against the Yazidi community .